LITERATUR REVIEW : INTRODUCTION OF THE CANINE INFLUENZA VIRUS - Fedri Rell; Andi Magfira Satya Apada; Anak Agung Putu Jhoni Wahyuda; Baso Yusuf; Rian Hari Suharto; Abdul Wahid Jamaluddin; Rasdiyanah; Adryani Ris (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
The Canine Influenza Virus (CIV) is a causative agent of flu in dogs and belongs to the highly mutable Type A influenza virus group, which also infects various animals and humans. Despite ongoing efforts to control it, genetic variations in Type A influenza viruses persist. This paper aims to provide practitioners, pet owners, academics, and policymakers with a concise overview of CIV to support early prevention, treatment, and containment strategies, particularly in Indonesia. The data presented in this paper are derived from scientific reports on canine flu cases caused by Type A influenza subtypes H3N8 and H3N2. The first reported case of H3N8 CIV infection occurred in the early 2000s in the United States, primarily affecting Greyhound dogs. This strain originated from an equine influenza outbreak in America. Meanwhile, the H3N2 subtype, which later emerged in dogs in the U.S., shares genetic similarities with strains isolated in China and South Korea, suggesting intercontinental transmission. Clinical signs of CIV infection are typically mild and resemble general flu symptoms but may worsen with secondary infections. As a zoonotic virus, CIV poses a potential threat to public health if left unaddressed. Thus, further investigation into canine influenza cases in Indonesia is essential, along with public education on vaccination and stricter regulations on the movement of animals from affected countries.